Cholinergic Control of Inflammation, Metabolic Dysfunction, and Cognitive Impairment in Obesity-Associated Disorders: Mechanisms and Novel Therapeutic Opportunities - Chang, Eric H.; Chavan, Sangeeta S.; Pavlov, Valentin A. (Frontiers in Neuroscience, 2019)
Obesity and obesity-associated disorders have become world-wide epidemics, substantially increasing the risk of debilitating morbidity and mortality. A characteristic feature of these disorders, which include the metabolic syndrome (MetS) and type 2 diabetes, is chronic low-grade inflammation stemming from metabolic and immune dysregulation. Inflammation in the CNS (neuroinflammation) and cognitive impairment have also been associated with obesity-driven disorders. The nervous system has a documented role in the regulation of metabolic homeostasis and immune function, and recent studies have indicated the important role of vagus nerve and brain cholinergic signaling in this context. In this review, we outline relevant aspects of this regulation with a specific focus on obesity-associated conditions. We outline accumulating preclinical evidence for the therapeutic efficacy of cholinergic stimulation in alleviating obesity-associated inflammation, neuroinflammation and metabolic derangements. Recently demonstrated beneficial effects of galantamine, a centrally-acting cholinergic drug and cognitive enhancer, in patients with MetS are also summarized. These studies provide a rationale for further therapeutic developments using pharmacological and bioelectronic cholinergic modulation for therapeutic benefit in obesity-associated disorders.